PERAN DINAS PERIKANAN KOTA BEKASI DALAM PEMBERDAYAAN PETERNAK IKAN HIAS DI KECAMATAN RAWALUMBU - Muhammad Syamsul Arifin (PANDITA : Interdisciplinary Journal of Public Affairs, 2021)
The role of the government at this time has not been accompanied by optimizing the utilization of existing potentials and involving the community in the utilization of the fishery sector. This causes an increase in fishery potential needs to be done, one of the potential utilization of fisheries that have the opportunity to be improved is ornamental fish. One of the main tasks of local government and its devices is community empowerment. To analyze the role of the government using the Theory presented by Yusuf, namely the role of the government as regulators, dynamicators, and facilitators. The results of this study explain the role of the government in the empowerment of ornamental fish farmers in Rawalumbu sub-district has not been optimal because there is no regulation governing governance in the center of ornamental fish promotion Rawalumbu Subdistrict, lack of human resources in the extension of aquaculture, then the absence of research centers and supporting facilities for extension teams in empowering ornamental fish breeders and the uneven empowerment of ornamental fish farmers in the city of Bekasi, especially in rawalumbu subdistrict.